Wnt3a signaling promotes proliferation, myogenic differentiation, and migration of rat bone marrow mesenchymal stem cells - Shang Yan-chang; Wang Shu-hui; Xiong Fu; Zhao Cui-ping; Peng Fu-ning; Feng Shan-wei; Li Mei-shan; Li Yong; Zhang Cheng (Acta Pharmacologica Sinica; Vol 28, No 11 (November 2007): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of the wingless-related MMTV integration site 3A (Wnt3a) signaling on the proliferation, migration, and the myogenic and adipogenic differentiation of rat bone marrow mesenchymal stem cells (rMSC). Methods: Primary MSC were isolated and cultured from Sprague-Dawley rats and characterized by flow cytometry. Mouse L cells were transfected with Wnt3a cDNA, and conditioned media containing active Wnt3a proteins were prepared. Cell proliferation was evaluated by cell count and 5-bromodeoxyuridine incorporation assay. The migration of rMSC was performed by using a transwell migration and wound healing assay. The myogenic and adipogenic differentiation in rMSC were examined by light microscopy, immunofluorescence, and RT-PCR at different time points after myogenic or adipogenic introduction. Results: Wnt3a signaling induced β-catenin nuclear translocation and activated the Wnt pathway in rMSC. In the presence of Wnt3a, rMSC proliferated more rapidly than the control cells, keeping their differentiation potential. Moreover, Wnt3a signaling induced 2.62% and 3.76% of rMSC-expressed desmin and myosin heavy chain after being cultured in myogenic medium. The myogenic differentiation genes, including Pax7, MyoD, Myf5, Myf4, and myogenin, were activated after Wnt3a treatment. On the other hand, Wnt3a inhibited the adipogenic differentiation in rMSC through the downregulated expression of CCAAT/enh ancer-binding protein alpha (C/EBPalph a) and peroxisome proliferator-activated receptor gamma (PPARgamma). Furthermore, Wnt3a promoted the migration capacity of rMSC. Conclusion: The results indicate that Wnt3a signaling can induce myogenic differentiation in rMSC. Wnt3a signaling is also involved in the regulation of the proliferation and migration of rMSC. These results could provide a rational foundation for cell-based tissue repair in humans.